2013
DOI: 10.1007/s11033-013-2535-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of single nucleotide polymorphisms in the agouti signaling protein (ASIP) gene in some goat breeds in tropical and temperate climates

Abstract: The agouti-signaling protein (ASIP) plays a major role in mammalian pigmentation as an antagonist to melanocortin-1 receptor gene to stimulate pheomelanin synthesis, a major pigment conferring mammalian coat color. We sequenced a 352 bp fragment of ASIP gene spanning part of exon 2 and part of intron 2 in 215 animals representing six goat breeds from Nigeria and the United States: West African Dwarf, predominantly black; Red Sokoto, mostly red; and Sahel, mostly white from Nigeria; black and white Alpine, brow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Mutations in the MC1R gene have been associated with coat colors variation in pigs2324, cattle25, and goats26. As an antagonist to MC1R to stimulate pheomelanin synthesis, ASIP has been implicated as a strong candidate gene that controls coat color patterns in goats and sheep272829. MITF is a key regulator of melanocyte development and is associated with various coat patterns in mammals30.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in the MC1R gene have been associated with coat colors variation in pigs2324, cattle25, and goats26. As an antagonist to MC1R to stimulate pheomelanin synthesis, ASIP has been implicated as a strong candidate gene that controls coat color patterns in goats and sheep272829. MITF is a key regulator of melanocyte development and is associated with various coat patterns in mammals30.…”
Section: Resultsmentioning
confidence: 99%
“…This variation in coat color was highly represented in the 14 Draa samples used in this study (Table S4 ). However, previous studies focussing on this gene identified an important polymorphism in worldwide goat breeds without any clear association with differences in coat color (Badaoui et al, 2011 ; Adefenwa et al, 2013 ). Fontanesi et al ( 2009b ) reported the presence of a copy number variation (CNV) affecting ASIP and AHCY genes, and might be associated to the white color in Girgentana and Saneen breeds.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, livestock play important roles in religious ceremonies and festivals such as marriages, naming ceremonies and traditional worship activities (Adefenwa et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%